2012
DOI: 10.1186/1465-9921-13-74
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced DNA hypermethylation in human pulmonary fibroblasts is associated with Thy-1 promoter methylation and the development of a pro-fibrotic phenotype

Abstract: BackgroundPulmonary fibrosis is a debilitating and lethal disease with no effective treatment options. Understanding the pathological processes at play will direct the application of novel therapeutic avenues. Hypoxia has been implicated in the pathogenesis of pulmonary fibrosis yet the precise mechanism by which it contributes to disease progression remains to be fully elucidated. It has been shown that chronic hypoxia can alter DNA methylation patterns in tumour-derived cell lines. This epigenetic alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 38 publications
6
74
0
Order By: Relevance
“…When the methylation was reversed with 5-aza-2'-deoxycytidine, Thy-1 expression was restored. This provides evidence that methylation alterations can influence myofibroblast differentiation (Robinson et al, 2012). It has also been shown in idiopathic lung fibrosis that there is hypermethylation of the p14 ARF promoter compared to controls, leading to reduced expression.…”
Section: Methylationsupporting
confidence: 52%
“…When the methylation was reversed with 5-aza-2'-deoxycytidine, Thy-1 expression was restored. This provides evidence that methylation alterations can influence myofibroblast differentiation (Robinson et al, 2012). It has also been shown in idiopathic lung fibrosis that there is hypermethylation of the p14 ARF promoter compared to controls, leading to reduced expression.…”
Section: Methylationsupporting
confidence: 52%
“…Studies revealed mechanistic links between aging and lung fibrosis involving telomere attrition, genomic instability, and epigenetic alterations (24)(25)(26). Antihistone antibodies, a type of ANA, are correlated with severe pulmonary fibrosis in systemic sclerosis patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, hypoxia can also induce histone modification and chromatin remodeling via hypoxia-inducible factor-independent pathways, indicating that additional mechanisms of epigenetic regulation can shape the cellular response to restricted oxygen supply (9,10), and potentially increase cell survival and promote angiogenesis in hypoxic conditions (11)(12)(13)(14). Hy-poxia-induced changes in the composition of the chromatinassociated proteome (chromatome) are therefore likely to alter gene expression and promote clonal evolution in developing tumors.…”
mentioning
confidence: 99%